Comparative analysis of cervical disease progression in HIV positive women receiving ART and those not receiving ART in Cape Town, South Africa, from 2002 to 2011 - Paulsen, Janis (Department of Public Health and Family Medicine, 2016)
Human papilloma virus (HPV) has been shown to be a necessary cause for the development of cervical cancer. Cervical cancer is a progressive disease, going through pathologically distinct stages ranging from normal cytology to malignancy. Precancerous lesions (low and high grade squamous epithelial lesions (SIL)) are detectable and treatable. In addition, women who are infected with human immunodeficiency virus (HIV) have been shown to be more likely to be infected with HPV than their HIV negative counterparts. Cervical cancer precancerous lesions have also been shown to be more commonly detected in HIV positive than in HIV negative women. Cervical cancer is classified as an acquired immunodeficiency syndrome (AIDS)-defining illness. The advent of antiretroviral therapy (ART) has seen an increase in the life span of HIV positive women. The use of ART has also seen a decline in the incidence of other AIDS-defining illnesses, such as Kaposi sarcoma and non-Hodgkin's lymphoma. Thus, a reduction in the incidence of cervical cancer among HIV positive women using ART is expected. However, the research thus far has been controversial, with some studies showing an increase in the incidence of cervical cancer in HIV positive women, others showing a decrease and still others showing no difference in the incidence. The aim of this project was to determine the incidence of precancerous lesions in HIV positive women receiving ART and to compare this to HIV positive women who are not receiving ART. Four hundred HIV positive women were enrolled into the MACH (Management of abnormal cytology in HIV-positive women) study from two primary health care clinics and one colposcopy clinic, in Cape Town, South Africa. Enrolment into the study was dependent on cervical screening naivety. At the time of enrolment, ART was not available to these women. However, as ART was rolled out in South Africa, women meeting ART eligibility criteria (at the time, CD4 count ≤ 200 cells/ml) were started on ART. Women were followed up at 6 monthly intervals, at which point cervical smears were taken and appropriate referral for colposcopy was done. Composite diagnoses were generated using both the visual colposcopy result and the histology result, where available. Women were dichotomized into ART and non- ART groups. Survival analysis was used to determine the time taken from normal cytology to incident SIL. Entrance into the survival analysis was dependent on a baseline cytological/histological diagnosis of normal. Thus 177 out of the 400 women were included. Follow up was censored at the first of SIL detection and treatment for SIL. A Cox model was built to determine the hazard for SIL development. This hazard was adjusted for ART status, CD4 count and age. CD4 count was treated as a time varying covariate. Women older than 40 years had a showed a 58% reduction in the progression of cervical disease from normal to SIL compared to women younger than 40 years. Women with baseline CD4 counts > 500 cells/ml had a 67% decrease in SIL development compared to those with a baseline CD4 count ≤ 200 cells/ml. Similarly, those with CD4 counts between 201 and 500 cells/ml showed a 35% reduction in cervical disease progression. The unadjusted incidence rate of SIL in women not receiving ART was 28.5 per 100 person years and in women who had initiated ART it was 30.82 per 100 person years. There was therefore no difference in the incidence rate of SIL between the 2 groups (RR=1.08; 95% CI 0.64-1.75). The unadjusted hazard ratio for progression to SIL was 1.3 (0.5-3.2) for those receiving ART compared to those not receiving ART. Adjusting for CD4 count and age, the hazard ratio was 0.9 (0.4-2.5). The adjusted hazard ratio for SIL development with a CD4 count > 200 cells/ml was 0.5 (0.2-0.9) compared to a CD4 count ≤ 200 cells/ml. The adjusted hazard ratios for age 30-39 years and ≥ 40 years were 0.9 (0.6-1.5) and 0.4 (0.2-0.9) respectively, compared to age < 30 years. ART has been scaled up and since the start of its roll out, the eligibility criteria has changed from CD4 count ≤ 200 cells/ml to CD4 count ≤ 350 cells/ml. The longevity of HIV positive women can approach that of HIV negative women if ART initiation is started early enough. In light of this and of the fact that cervical lesions are more frequently detected in HIV positive women, cervical screening and referral services should be strengthened.